Characterization of Neural Stem/Progenitor Cells Expressing VEGF and its Receptors in the Subventricular Zone of Newborn Piglet Brain - Ara, Jahan; Fekete, Saskia [UNESP]; Zhu, Anli; Frank, Melissa (Springer/plenum Publishers, 2010)
Neural stem/progenitor cell (NSP) biology and neurogenesis in adult central nervous system (CNS) are important both towards potential future therapeutic applications for CNS repair, and for the fundamental function of the CNS. In the present study, we report the characterization of NSP population from subventricular zone (SVZ) of neonatal piglet brain using in vivo and in vitro systems. We show that the nestin and vimentin-positive neural progenitor cells are present in the SVZ of the lateral ventricles of neonatal piglet brain. In vitro, piglet NSPs proliferated as neurospheres, expressed the typical protein of neural progenitors, nestin and a range of well-established neurodevelopmental markers. Upon dissociation and subculture, piglet NSPs differentiated into neurons and glial cells. Clonal analysis demonstrates that piglet NSPs are multi-potent and retain the capacity to generate both glia and neurons. These cells expressed VEGF, VEGFR1, VEGFR2 and Neuropilin-1 and -2 mRNAs. Real time PCR revealed that SVZ NSPs from newborn piglet expressed total VEGF and all VEGF splice variants. These findings show that piglet NSPs may be helpful to more effectively design growth factor based strategies to enhance endogenous precursor cells for cell transplantation studies potentially leading to the application of this strategy in the nervous system disease and injury.
Keywords: Neural stem/progenitor cells; Subventricular zone; Proliferation; Newborn brain; Piglet; VEGF